Morte e decomposição biográfica em Memórias Póstumas de Brás Cubas - Silva Junior, Augusto Rodrigues da (2008)
The most remarkable fact in Brás Cubas life is his death. Such peculiarity illustrates the creation of a peculiar method used by Machado de Assis: the deceased author. The author s analysis of To The Reader debates the feelings and reasons of the one who writes to alive people and verifies how much the Self-conscience Genre contributed in the oblique and concealing construction of the work; an autobiography that presents someone in transformation and that allows people to evaluate the importance of the biographer s formation on the other characters (e.g. The father, Virgília, and Quincas Borba). Finally, a talking deceased group of people analysis proves the organic unit of that tradition, maps out different carnival perceptions, and the discursive freedom expression. The authorial death dialogues with: epic catabasis, the menipeica satire, the feast during the medieval funerals, the abundant happiness in Rabelais, and manifestations of modernity, including the tale Bobók written by Dostojévski (XIX). The fusion of the disfigured laughing with the septic negativity, discusses what is the most significant for a human being: its existence. Converging out set fantasy and reality, Memórias Póstumas de Bras Cubas breaks the usual romance limits and announces the ironic and melancholic language that decomposes the eternal human contradictions.